ДОСЛІДЖЕННЯ ПЕРЕНОСУ АКТИВНОЇ ПОТУЖНОСТІ В УСТАНОВЦІ ІНДУКЦІЙНОЇ ТЕРМООБРОБКИ ЦИЛІНДРИЧНИХ АЛЮМІНІЄВИХ ЗАГОТОВОК З ТРИФАЗНИМ ІНДУКТОРОМ - Жаркін, А.Ф.; Гориславець, Ю.М.; Глухенький, О.І.; Білянін, Р.В. (Інститут електродинаміки Національної академії наук України, 2025)
For the proposed design variant of a three-phase inductor of a device for induction heat treatment of cylindrical aluminum billets, which is used in the technology of production of conductive cores of power cables before pressing of wire rod, using the developed mathematical model of electrothermal processes, the process of active power transfer between phase sections and along the length of the billets, which occurs in the inductor due to inductive coupling between phase windings, has been investigated. It was established that the side phase sections of the inductor are characterized by the lack of balance between the active power consumed from the power supply network and the total heat dissipation in the phase section and the corresponding part of the aluminum billet, while this balance is fulfilled for the central phase section and the inductor as a whole. The distribution along the length and radius of the induction installation of the axial component of the electromagnetic field energy flux density vector was obtained, which confirms the presence of active power transfer between adjacent phase sections of the three-phase inductor and indicates its absence along the aluminum billets (on the secondary side of the system). It was established that the transfer of active power between the phase sections of the inductor has practically no effect on the heating of the aluminum billets. It was determined that the negative consequence of the transfer of active power between the phase sections of the three-phase inductor is the uneven load of the phases of the electrical network. A rational power supply scheme for a three-phase three-layer inductor from a three-phase industrial electrical network is proposed, which provides the maximum possible energy efficiency of the induction installation with minimal unevenness of the phases load of the electrical network. Ref. 9, fig. 6, table.